Структура капіталу підприємств: систематизація теоретичних підходів у концепції стабілізації національної економіки - Халатур, Світлана Миколаївна; Khalatur, Svitlana; Яценко, Катерина; Yatsenko, Kateryna (Чорноморський національний університет імені Петра Могили, ТОВ `ДКС Центр`, 2022)
У статті розглянуто сучасні теорії систематизації підходів до структури капіталу підприємству контексті стабілізації національної економіки, і на цій основі визначено детермінанти струк-тури капіталу. Діяльність підприємств є значним економічним внеском у країну. Однак розви-ток і розширення фінансово стійких підприємств залежить від їх адекватного фінансування такапіталізації. Рішення щодо структури капіталу відображає широкий спектр операцій керівниц-тва підприємства. Таким чином, метою цієї роботи є аналіз структури капіталу підприємств тавизначення факторів, що впливають на неї. Отже, для розуміння того, як підприємства фінан-сують свою діяльність, необхідно вивчити детермінанти їхньої діяльності, рішення щодо фінан-сування або структури капіталу. Структура капіталу визначена як поєднання боргу та власногокапіталу, що використовується для фінансування бізнес-операцій. The article examines modern theories of systematization of approaches to the capital structure ofenterprises in the context of stabilization of the national economy, and on this basis, the determinantsof the capital structure are determined. Business activity is a significant economic contribution tothe country. However, the development and expansion of financially stable enterprises depends ontheir adequate financing and capitalization. The decision on the capital structure reflects a widerange of operations of the company's management. Thus, the purpose of this work is to analyze thecapital structure of enterprises and determine the factors affecting it. Therefore, to understand howcompanies finance their activities, it is necessary to study the determinants of their activities,financing decisions or capital structure. Capital structure is defined as the combination of debt andequity used to finance business operations. One of the key financial decisions of any organization is the search for funding sources. Thesedecisions depend on many internal and external factors. The influence of these factors on therelationship between equity and debt was the subject of research. There are many theories of capitalstructure. The most prominent theories include: the Modigliani-Miller model, signaling theory, agencytheory, action order theory, and static trade-off theory.The capital structure depends on the share of fixed assets in the total assets of the enterprise, itssize, profitability, and liquidity. Profitability is statistically significant only in the case of short-termdebt, which indicates that more profitable enterprises resort to less debt use and rely more on internalfunds. The growth variable is significant only for large enterprises. The negative relationship withthe short-term perspective shows that large enterprises prefer debt financing for long-term growth.Liquidity is very important for businesses, especially in the short term. The number of years in businessmatters for secured financing. In general, measuring the performance of a business means evaluatingits ability to achieve its goals in an optimal way.
Capital structure of enterprises: systemazation of theoretical ap proachesin the context of stabilization of the national economy
Keywords: результативність бізнесу; business performance; структура капіталу; capital structure; показники; indicators; модель; model